LA ORALIDAD COMO BASE CULTURAL DE LOS HABITANTES DEL MUNICIPIO SUCRE (De la Crítica, 2024)
This article is based on a documentary review of existing theories regarding oral tradition, addressing the issue of orality as the basis of the culture of the inhabitants of the Sucre Municipality, emphasizing poetry as a means of transmission and conservation of local customs and traditions.